Values beyond entertainment audience reception on satirical film "Ded na si lolo" - Albesa, Adrianne; Dusaban, Edwin Jr.; Paguntalan, Angela (2015.)
This study looks into whether or not film enthusiasts recognize socio-cultural verisimilitude in the film Ded na si Lolo. The respondents of this study are film enthusiasts from the University of the Philippines Visayas who are active filmmakers and participate film festivals in Western Visayas. Data collection is done in two sessions of focus group discussion with a total of 12 participants. The film Ded na si Lolo is shown to the participants after which they are asked open-ended questions on their perception. Responses are coded and interpreted through thematic analysis. An observation in this research is that the encoded message in the film is easily decoded if the viewers are familiar with the film elements (i.e. characters, setting, plot, etc.) and also with real life issues and scenarios. However, being too familiar with film elements puts the viewer at risk of misinterpreting the message content or assigning meanings that were not intended by the filmmaker. All are able to recognize the socio-cultural verisimilitude of the film Ded na si Lolo and most of the audience, still, are able to decode the encoded message of the filmmaker. The results imply that Ded na si Lolo, being satirical in nature, has not been very successful in delivering its message to criticize the funeral customs and beliefs of the Philippine culture. The study conclude that if the satirical purpose of the film is not fully grasped by film enthusiasts who have the ability to analyze and decode messages from the film, this might be even more challenging for the general population.
Thesis -- Bachelor of Arts in Communication and Media Studies. University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Entertainment -- Values; Ded na si Lolo -- Satirical Film; Satire Film; Socio-Cultural verisimilitude; Audience reception